Machiavelli : the prince - Machiavelli, Niccolò, 1469-1527; Skinner, Quentin; Price, Russell (Cambridge : Cambridge University Press, 2019)
This new edition of the acclaimed translation of Niccolò Machiavelli's The Prince - revised for the first time after thirty years - includes a rewritten and extended introduction by Quentin Skinner. Niccolò Machiavelli is arguably the most famous and controversial figure in the history of political thought. The Prince remains his best-known work, and throws down a challenge that subsequent writers on statecraft and political morality have found impossible to ignore. Quentin Skinner's introduction offers a lucid analysis of Machiavelli's text both as a response to the world of Florentine politics and as a critical engagement with the classical and Renaissance genre of advice-books for princes. This new edition also features an improved timeline of key events in Machiavelli's life, helping the reader place the work in the context of its time, in addition to an enlarged and fully updated bibliography.
Machine generated contents note: Editorial note; Introduction; Principal events in Machiavelli's life; Bibliographical note; Translator's note; Map: northern and central Italy, c. 1500; Dedicatory letter: Niccol- Machiavelli to His Magnificence Lorenzo de' Medici; I How many kinds of principality there are, and by what means they are acquired; II Hereditary principalities; III Mixed principalities; IV Why the Kingdom of Darius, which Alexander occupied, did not rebel against his successors after Alexander's death; V By what means cities or provinces that lived under their own laws before they were occupied ought to be administered; VI New principalities acquired by one's own arms and ability; VII New principalities acquired through the arms and fortune of others; VIII Those who become rulers through crime; IX The civil principality; X In what ways the strengths of all principalities should be measured; XI Ecclesiastical principalities; XII How many kinds of soldiers there are, and mercenary troops; XIII Auxiliaries, mixed troops and one's own troops; XIV How a ruler should act concerning military matters; XV The things for which men, and especially rulers, are praised or blamed; XVI Liberality and parsimony; XVII Cruelty and mercifulness; and whether it is better to be loved than feared, or the contrary; XVIII In what way rulers should keep their promises; XIX How contempt and hatred should be avoided; XX Whether building fortresses, and many other things that rulers frequently do, are useful or useless; XXI What a ruler should do in order to be thought outstanding; XXII On those whom rulers employ in secret matters; XXIII How flatterers should be shunned; XXIV Why the rulers of Italy have lost their states; XXV How much control fortune has over human affairs, and by what means she can be resisted; XXVI An exhortation to seize possession of Italy and assert her liberty from the barbarians; Appendix A Letters relevant to The Prince; Appendix B Notes on the vocabul
Title from publisher's bibliographic system (viewed on 17 Jul 2020).
Keywords: elektronické knihy; electronic books; Political science -- Philosophy -- Early works to 1800.; Political ethics -- Early works to 1800.; State, The -- Early works to 1800.